Carbon mineralization in Laptev and East Siberian sea shelf and slope sediment; Biogeosciences; Vol. 15, iss. 2 - Bruchert V. Volker; Broder L. Lisa; Sawicka J. E. Joanna; Tesi T. Tommaso; Joye S. P. Samantha; Sun X. Xiaole; Semiletov I. P. Igor Petrovich; Samarkin V. A. Vladimir (2018, 2018)
Title screen